Review effects of radiation treatment on HPV-related vulvar cancer: a meta-analysis and systematic review - Li, Wei; Zhai, Lijun; Zhu, Yinju; Lou, Fengjun; Liu, Shiyu; Li, Ke; Chen, Liang; Wang, Huankun (Frontiers in Oncology, 2024)
Objective. Vulvar carcinoma exhibits a robust correlation alongside HPV infection; however, the impact of HPV rank on the prognostic outcomes of radiation therapy within vulvar malignancies stays ambiguous. In the present study, we performed a comprehensive examination as well as meta-analysis to assess the influence of infection with HPV upon the long-term outlook as well as sensitivity of individuals with vulvar cancer undergoing radiation therapy.Methods. A meticulous examination of the existing research was conducted in accordance with the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A thorough search was conducted in the PubMed, Embase, Web of Science, as well as Cochrane Library databases, covering the entire available literature till April 1, 2023. The studies that met the inclusion criteria contained data about HPV infection and oncological outcomes in patients with vulvar cancer who received radiation therapy. This study was registered in PROSPERO (CRD42023417957).Results. We identified 12 retrospective studies meeting our inclusion criteria, which included a total of 3967 patients. Patients with HPV-associated vulvar cancer achieved a better overall survival rate after radiotherapy (HR=0.71, 95%CI: 0.54-0.93, P=0.01HR=0.74, 95% CI: 0.57-0.95, P=0.02), butand showed a no significant improvement in disease-free survival (HR=0.75, 95%CI: 0.58-0.97, P=0.09HR=1.33, 95% CI: 0.93-1.91, P=0.11) orand progression-free survival (HR=0.31, 95%CI: 0.22-0.45, P,<0.01HR=0.58, 95% CI: 0.33-1.04, P=0.07). HoweverMeanwhile, the complete remission rate after radiotherapy was lowerhigher for HPV-associated vulvar cancer patients (M-H=4.02, 95% CI: 1.87-8.61, P=0.0003), and the local control rate was worsebetter (HR=1.90, 95% CI: 1.15-3.15, P=0.01), exhibiting an reduced elevated incidence of relapse within the field of study (HR=0.21, 95% CI: 0.10-0.42, P<0.001).In comparison to HPV-independent vulvar squamous cell carcinoma, patients with HPV-associated vulvar cancer exhibit lowerhigher sensitivity to radiotherapy, with a no significant difference in prognosis. Further research should investigate the mechanisms underlying this lowhigh sensitivity to radiotherapy caused by HPV, and should be evaluated using high-quality randomized controlled trials.